Deciphering the folate puzzle: Unraveling the impact of genetic variations and metabolites on cancer risk - Liu, Tong; Liu, Chen‐An; Wei, Ya‐Ping; Song, Meng‐Meng; Zhang, Qi; Song, Yun; Chen, Ping; Liu, Li‐Shun; Wang, Bin‐Yan; Shi, Han‐Ping (International journal of cancer, 2024)
The C677T polymorphism in the MTHFR gene and its role in folate metabolism, impacting serum folate metabolites like THF and 5‐MTHF, is a critical but underexplored area in cancer research. This nested case–control study utilized data from CHHRS, involving 87,492 hypertensive adults without prior cancer. During a median of 2.02 years, we identified 1332 cancer cases and matched controls based on age, sex, and residency. Serum levels of folate, THF, and 5‐MTHF were measured, and the MTHFR C677T gene polymorphism was considered. Statistical analyses included restricted cubic spline regression and conditional logistic regression models. Serum THF levels were inversely associated with overall cancer risk (ORper SD = 0.90, 95% CI = 0.82–0.99), while 5‐MTHF levels showed a negative association in the general cohort (ORQ3 vs. Q1 = 0.76, 95% CI = 0.60–0.96; ORQ4 vs. Q1 = 0.75, 95% CI = 0.58–0.98) and in individuals with MTHFR C677T (CC + CT) polymorphism (ORper SD = 0.87, 95% CI = 0.77–0.99; ORQ4 VS. Q1 = 0.79, 95% CI = 0.61–0.98), but a positive association in the MTHFR C677T (TT) subgroup (ORper SD = 1.89, 95% CI = 1.02–3.72; ORQ4 VS. Q1 = 2.17, 95% CI = 1.06–8.21). The impact of folate, THF, and 5‐MTHF on cancer risk varied significantly across different cancer types and MTHFR C677T genotypes. This study provides novel insights into the variable effects of folate and its metabolites on cancer risk, influenced by genetic factors like the MTHFR C677T polymorphism and cancer type. What's new? This study investigates the relationship between serum folate, THF, and 5‐MTHF levels and cancer risk, showing that folate's effect varies by genetic background and cancer type. Elevated THF levels correlate with decreased cancer risk. Importantly, the impact of 5‐MTHF on cancer risk depends on MTHFR C677T polymorphisms, offering protection in CC and CT genotypes but potentially increasing risk in TT genotypes. These findings highlight folate's complex role in cancer biology and the need for further research to understand these interactions.